Data-Governance Approach Implemented in the Activities of State Supervisory Authorities of the Russian Federation - Ekaterina Sviridova (Современные информационные технологии и IT-образование)
The article analyzes the importance of the data management process in the activities of state supervisory authorities of the Russian Federation. A definition of the concept “data lake” is given. The main elements and stages of the constructed data lake of the Accounts Chamber of the Russian Federation are highlighted. The process of working with data that is used by the inspector staff of the SP of the Russian Federation to carry out control and expert-analytical activities is described. The main results of the work with data by the inspectors of the SP of the Russian Federation are summed up. The weak points of the constructed storage facility were analyzed. As a solution to the problem of “pollution” of a data lake, the data governance approach is considered, its definition is given, the essence of the concept is described, and the main problems solved by this approach are highlighted. The Russian market for IT solutions in the field of data and metadata management is analyzed, and their functionality is described. Open source solutions that can also be used for data management are also considered. Some of the solutions presented on the Russian market previously existed only as internal development, but the demand for their functionality made it possible to bring them to the market (SIBUR IT solution, Data Detective). The qualitative and quantitative results of the work of the Accounts Chamber of the Russian Federation for 2022 are considered, taking into account the implementation of the data governance approach. A comparison was made of the results of the work of the Russian Joint Venture for 2021 and 2022. The successes of commercial organizations in implementing the data governance approach to data management are considered. The influence of the implementation of the data governance approach in commercial organizations on the quality of control and expert-analytical activities of the state supervisory authorities of the Russian Federation is traced. The positive results of implementing the approach are described.